Revisión del estado del arte de los sistemas de monitoreo para la prevención de desastres naturales en el Ecuador - Palma Aguiar, Iván Alejandro (2018)
The purpose of this document is to disclose the current state of the early warning systems in Ecuador, for the mitigation of natural disasters, based on interviews with experts from the Geophysical Institute of the National Polytechnic University, personnel in charge of the systems of INAMHI monitoring, INOCAR technicians, responsible for the monitoring of the Municipality of Canton Rumiñahui ,personnel in charge of the risk management of the ECU911, as well as, recognized geological experts in the country. Field visits were made, where it was possible to verify the status of the equipment used to collect data and monitor the different phenomena, as well as the monitoring centers run by the different organizations, where the information is collected and is processed to keep historical records that can be presented and, if applicable, issue the corresponding alert to the population. We also investigated different projects that have been developed by universities, private and public companies, to mitigate the impacts of natural disasters in vulnerable areas, taking technological development as the main axis. There is a theoretical introduction of early warning systems, their different definitions, importance, implementation and types that may exist. Also, you can find an extract of the different natural threats. In addition, a summary of the legal framework is presented, in which reference is made to the articles, codes and regulations that establish guidelines and guidelines for proper Risk Management. A compilation of information was made, of what is within the national territory, the early warning systems, the equipment that has been implemented or that are part of it, noting that certain places or areas have a greater number of equipment than others, making known the different aspects and realities, in regard to monitoring systems, as well as the deficiencies in the technological and economic part of governmental or private institutions for the development of these systems. Finally, the conclusions derived from the research carried out are presented, as well as the recommendations that have come to be clarified by the development of the investigation, which presents the current reality and the shortcomings that are found, both in the technological part as in the economic part, for the improvement of the early warning systems and therefore obtain a better response time, both from the citizenship and from the entities in charge of the different processes that may be generated by the emergency.